phzO, a Gene for Biosynthesis of 2-Hydroxylated Phenazine Compounds in Pseudomonas aureofaciens 30-84 - Delaney, Shannon M. (American Society for Microbiology, 2001)
Certain strains of root-colonizing fluorescent Pseudomonas spp. produce phenazines, a class of antifungal metabolites that can provide protection against various soilborne root pathogens. Despite the fact that the phenazine biosynthetic locus is highly conserved among fluorescent Pseudomonas spp., individual strains differ in the range of phenazine compounds they produce. This study focuses on the ability of Pseudomonas aureofaciens 30-84 to produce 2-hydroxyphenazine-1-carboxylic acid (2-OH-PCA) and 2-hydroxyphenazine from the common phenazine metabolite phenazine-1-carboxylic acid (PCA). P. aureofaciens 30-84 contains a novel gene located downstream from the core phenazine operon that encodes a 55-kDa aromatic monooxygenase responsible for the hydroxylation of PCA to produce 2-OH-PCA. Knowledge of the genes responsible for phenazine product specificity could ultimately reveal ways to manipulate organisms to produce multiple phenazines or novel phenazines not previously described.